Schools “Detached” from Reality. On the Architectonics and Dynamics of Contemporary Educational Space - Włodarczyk, Rafał (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2019)
Each institutionalized social practice, including school practice, is placed in a separate temporal, spatial and situational context appropriate for itself. In this way a distance is created between school education and social reality. This distance is changing under the influence of developments in the organization of schools and social practices. A number of studies reveal the negative effects of the increasing distance between school education and social practice. The aim of this paper is to show three dimensions in which the distance between school education and social reality is formed.
Keywords: bureaucracy; experience; distance; school education; ideology; social practice; social realities; social structure